Analisi Hasil Karya Ecoprint Teknik Pounding Pada Pembelajaran SBdP Kelas II SDN 04 Seberang Musi - Wasa, Meitri Nersa Farama; Kurniawati, Ike (JURIDIKDAS, 2024)
This research aims to describe the results of ecoprint artwork using the pounding technique in Arts and Crafts learning for second-grade students at SDN 04 Seberang Musi. The study adopts a qualitative approach with a descriptive method. The subjects of the research are second-grade students at SDN 04 Seberang Musi. The research instrument used by the researcher includes guidelines for observing meticulous attitudes, observing artwork results, and interview guidelines. Data collection techniques involve observation, interviews, and documentation, with data validity ensured through triangulation. The research findings indicate that the ecoprint artwork created by students already encompasses elements of visual arts and principles of visual arts. However, unity principles in group one, contrast, and rhythm principles in each group's work are not yet evident. In conclusion, all visual arts elements in the works of each group are already visible, while some principles of visual arts are not yet fully manifested.